Bending response of lap welded steel pipeline joints. (December 2020) - Sarvanis, Gregory C.; Chatzopoulou, Giannoula; Fappas, Dimitris; Karamanos, Spyros A.; Keil, Brent D.; Lucier, Gregory; Gobler, Fritz; Mielke, Richard D.
Abstract: The paper presents a combined experimental and numerical investigation of the bending response of lap welded joints in pressurized steel water pipelines. It is motivated by the structural performance of large-diameter steel pipelines used for water transmission in seismic and geohazard areas, where the pipeline may be subjected to severe permanent ground-induced actions. A series of large-scale four-point bending experiments on lap welded joints has been performed, and rigorous finite element numerical models have been developed for conducting extensive numerical simulations. The numerical models account for the bell forming process and the corresponding residual stresses, as well as the presence of initial geometric imperfections on the pipeline wall. A very good comparison has been found between experimental results and numerical simulations in terms of both global response and local strains developed at the vicinity of the weld. The finite element models are also employed for elucidating some interesting features of lap welded joint behavior under severe bending deformation, towards determining the joint strength, its deformation capacity and the evolution of strain at different deformation stages. The experimental and numerical results indicate that lap welded joints, can sustain a significant level of bending deformation and strain, without loss of pressure containment, and can be used in geohazard areas, where severe permanent ground-induced strains on the pipeline wall are expected to develop. Highlights: Seven 24-inch-size internally-pressurized specimens were tested in bending. All specimens sustained significant deformation without loss of containment. Predicted values of force and strain are in excellent agreement with test data. Resistance of buckled specimens to cyclic pressure and burst has been excellent. Maximum bending moment of lap welded joints is about 80% of that of plain pipe.